2022
DOI: 10.3390/ma15186250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Preparation Conditions on the Catalytic Properties of CoPt for Highly Efficient 4-Nitrophenol Reduction

Abstract: CoPt alloys with Pt contents from 15 to 90% were prepared using low-cost electrochemical deposition. Different samples were synthesized from electrochemical baths at pH = 2.5 and 5.5 in a solution with and without saccharin as an additive. The morphology, composition and crystalline structure of the as-prepared samples were investigated by High Resolution—Scanning Electron Microscopy (HR-SEM), Atomic Force Microscopy (AFM), Ultra-high Resolution—Transmission Electron Microscopy (UHR-TEM), Energy-Dispersive X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…This data are in good agreement with those presented in Ref. [26]. As can be observed from Figure 3, all the as-deposited materials present diffractions peaks at 2Θ = 43.5 and 44.5.…”
Section: Coxpt100−x Thin Layer Microstructure Composition Crystalline...supporting
confidence: 92%
See 2 more Smart Citations
“…This data are in good agreement with those presented in Ref. [26]. As can be observed from Figure 3, all the as-deposited materials present diffractions peaks at 2Θ = 43.5 and 44.5.…”
Section: Coxpt100−x Thin Layer Microstructure Composition Crystalline...supporting
confidence: 92%
“…As additive, we used sodium saccharine 0.00389M. The electrodeposition process parameters (such as applied potential, time on and time off), as well as the electrochemical bath characteristics (such as composition, pH value and additives), have been selected based on previously obtained results [25,26], where we found that the saccharin addition into the electrochemical bath improves the thin film layer mechanical properties (the saccharin is a well-known additive used for smoothening and stress relieving electrodeposited thin films). We also found that the saccharine favors the preparation of the CoPt alloys with a hcp crystalline structure.…”
Section: Synthesis Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of p –nitrophenol as the target substance is justified both by the practical importance of the reaction, and by the fact that there are multiple and excellent studies that thus allow the comparative evaluation of the results [ 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of p -nitrophenol, with hydrogen obtained in situ from sodium borohydride (NaBH 4 ), was studied to determine the catalytic performance of various nanomaterials [ 14 , 15 , 16 , 37 , 38 , 39 , 40 , 45 ].…”
Section: Resultsmentioning
confidence: 99%